Humanization of CD47 enables development of functional human neutrophils via postirradiation remodeling of the bone marrow - Esen Sefik; William Philbrick; Fengrui Zhang; Kriti Agrawal; Brian Van Lee; Johannes Sam; Kutay Karatepe; Yunjiang Zheng; Kaixin Liang; Sophia Peng; Haris Mirza; Athreya Rangavajhula; et al. (Proceedings of the National Academy of Sciences, 2025)
Murine and human immune systems differ significantly, particularly within the myeloid lineage. Humanized mice, generated by transplanting human hematopoietic stem, progenitor cells into genetically modified mice, are invaluable to study human immune development and function in vivo. However, a major limitation of current models is suboptimal myelopoiesis, particularly lack of functional human neutrophils, hampering the modeling of human immune responses and chronic diseases. Here, we describe a humanized mouse model, named MaGIC for genes replaced, in the C57Bl/6 N strain, which improves human myelopoiesis and enables development of functional human neutrophils. In MaGIC mice, human cytokines M-CSF/CSF1(M), GM-CSF/CSF2(G) and IL-6(I) are knocked-in replacing mouse genes and murine IL2rg and Rag1 (a) are deleted. Human THPO in these mice supports human hematopoiesis. More importantly, insertion of human CD47 (C) under the control of endogenous mouse CD47 promoter enables xenotransplantation and human neutrophil development. MaGIC mice support all human neutrophil subsets found in human bone marrow and blood, a major improvement. This is achieved by creating a niche postirradiation for human granulocyte–macrophage progenitors via reduced murine CD47 and physiological levels of human CD47. These mice also have mature human monocytes, tissue macrophages, alveolar macrophages, dendritic cells, and NK cells, enabled by humanized M-CSF and GM-CSF. Human neutrophils in MaGIC mice are fully functional in chemotaxis, phagocytosis, reactive oxygen species production, and neutrophil extracellular trap formation in response to inflammation. MaGIC mice address critical gaps in current models and enable incisive translational research on human neutrophils, advancing studies in infectious, autoimmune, and inflammatory diseases.